2016
DOI: 10.3141/2602-12
|View full text |Cite
|
Sign up to set email alerts
|

Steer or Brake?: Modeling Drivers’ Collision-Avoidance Behavior by Using Perceptual Cues

Abstract: Driver models have been developed to capture collision-avoidance behaviors, yet there is a lack of understanding of what perceptual processes influence drivers’ choices to brake or steer. A statistical model of these decisions was developed with cluster analysis and multinomial logistic regression with data from a simulator study of drivers’ responses to rear-end collisions. Drivers’ choices of responses were clustered on the basis of the maximum values of the magnitude of braking and steering forces, starting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 25 publications
3
15
0
Order By: Relevance
“…• The BRTs significantly decrease with higher levels of kinematic criticality, both during driving with CC and ACC. This outcome is in line with previous research (Markkula, 2014;Markkula et al, 2016;Engström et al, 2017;Venkatraman et al, 2016) but shows for the first time this phenomenon in silent failures of automation. • The BRTs are significantly longer during driving with ACC compared to driving with CC.…”
Section: Discussionsupporting
confidence: 93%
“…• The BRTs significantly decrease with higher levels of kinematic criticality, both during driving with CC and ACC. This outcome is in line with previous research (Markkula, 2014;Markkula et al, 2016;Engström et al, 2017;Venkatraman et al, 2016) but shows for the first time this phenomenon in silent failures of automation. • The BRTs are significantly longer during driving with ACC compared to driving with CC.…”
Section: Discussionsupporting
confidence: 93%
“…Lastsecond braking and steering judgments in a car-following condition have been studied relative to the alert timing for forward collision warnings [17]. Focusing on the carfollowing scenario, a statistical model was developed to understand the perceptual processes involved in a driver's decision to brake or steer [18]. It was shown that, in imminent rear-end collision situations, most drivers tend only to brake and often do not attempt to avoid obstacles by steering.…”
Section: Introductionmentioning
confidence: 99%
“…A random-forest machine-learning technique was used to develop red-light-running violation-prediction models using a single objective indicator (time to intersection) [20]. Venkatraman et al applied cluster analysis and multinomial logistic regression to predict driver decisions in the carfollowing situation [18]. Generative approaches for maneuver prediction include various filtering methods, such as Kalman and particle filters, hidden Markov models, and dynamic Bayesian networks [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…In an overtaking scenario, being able to predict whether a driver would avoid collisions by braking (to initiate an accelerative maneuver) or by steering (to initiate a flying maneuver) can help active safety systems to tune intervention times [37], [38]. In fact, knowing a driver's overtaking strategy can also be valuable information for systems that aim at preventing a head-on collision with the oncoming traffic in the passing phase, as a result of a poorly timed flying maneuver [30], [32], and rear-end collisions with cyclists as a result of a poorly timed accelerative maneuver.…”
Section: Existing Research On Driver-cyclist Interaction In Overtamentioning
confidence: 99%